Pengembangan Perangkat Pembelajaran Pembuktian Menggunakan Model Pembelajaran Guided Inquiry untuk Meningkatkan Kemampuan Geometri Siswa Sekolah Menengah Atas - Lia Hamimi; M. Ikhsan; Zainal Abidin (Universitas Syiah Kuala, 2018)
Mathematical proof is one aspect that must be considered in learning mathematics in school. One of the obstacles that students experience on geometry is the difficulty of constructing proof. The specific learning materials are not available yet. To achieve that goal required a learning materials for teaching mathematical proof using Guided Inquiry model. This research is a developmental research using ADDIE model consisting of five stages, namely Analyze, Design, Development, Implementation, and Evaluation stage. The experimental subjects in this study were one class of students at year 12 at one of senior high school at Banda Aceh. Based on the results obtained that the learning materials consisting of lesson plan, students worksheet, handout, and test are categorized as valid, practical, and effective. The recommandation of this study is learning materials can be implemented for teaching mathematical proof in senior high school.